Principal Supervision Strategies in Improving Teacher Professionalism : Strategi Supervisi Kepala Sekolah Dalam Meningkatkan Profesionalisme Guru - Ikhwan, Muh. Saidil; Rabbani, Syarifah Aulia (Universitas Muhammadiyah Sidoarjo, 2024)
Teachers in providing knowledge to students must perform professionally. One way to increase teacher professionalism is to carry out teacher supervision. School principals must have special supervision strategies to increase teacher professionalism. The aim of this research is to determine the principal's supervision strategy in increasing teacher professionalism at MTs NW Dames. This research uses a descriptive qualitative approach that focuses on teacher professionalism. The subjects of this research include school principals, teachers and education staff at MTs NW Dames. The results of this research show that there are three supervision strategies carried out by school principals, namely 1) supervision strategy using coaching activities, 2) supervision strategy using mentoring activities, and 3) supervision strategy using workshop activities. Highlights: Coaching activities: Principals engage in hands-on guidance to improve teacher performance and professionalism, providing direct feedback and support. Mentoring activities: Principals foster long-term growth by offering personalized guidance and advice, building trust and rapport with teachers. Workshop activities: Principals facilitate collaborative learning environments through workshops, promoting skill development and sharing best practices among educators. Keywords: Supervision Strategy, Headmaster, Teacher Professionalism.